Protection of mexiletine against hypoxic damage of synaptic function in hippocampal slices - Zhang Xue-Song; Wang Tian-You (Acta Pharmacologica Sinica, 2016)
The evoked population spike (PS) and presynaptic fiber volley (PV) were recorded from the CA1 area in rat hippocampal slices. At the 3rd min of hypoxia, the amplitude of PS declined to 0.4 +/- 0.4 mV in control slices whereas to 1.2 +/- 1.2 mV or 1.5 +/- 0.4 mV in slices pretreated for 1 h with mexiletine (Mex) 10 or 100 mumol.L-1, respectively. Thirty min after reoxygenation the amplitude of PS recovered to 11.1% of its original level in control slices, but to 47.6% or 65.0% in slices pretreated with Mex 10 or 100 mumol.L-1 respectively. Thus Mex retarded the hypoxic declining of PS during hypoxia and accelerated the recovery of PS during reoxygenation. At normal conditions Mex 100 mumol.L-1 reversibly reduced the amplitude of PS and PV partially. Our results suggested that the inhibition of Mex on sodium current may play an important role in the mechanism of its protection against hypoxic damage.